Paternal Caregivers' Parenting Practices and Psychological Functioning among African American Youth Living in Urban Public Housing. Issue 3 (20th May 2016) - Doyle, Otima; Clark Goings, Trenette; Cryer‐Coupet, Qiana R.; Lombe, Margaret; Stephens, Jennifer; Nebbitt, Von E.
Abstract : Structural factors associated with public housing contribute to living environments that expose families to adverse life events that may in turn directly impact parenting and youth outcomes. However, despite the growth in research on fathers, research on families in public housing has practically excluded fathers and the role fathers play in the well‐being of their adolescents. Using a sample of 660 African American adolescents recruited from public housing, we examined the relationship between paternal caregivers' (i.e., fathers' and father figures') parenting practices and adolescents' depressive symptoms, attitudes toward deviance, and self‐efficacy. Using a latent profile analysis (LPA), we confirmed a four‐class model of paternal parenting practices ranging from high to low levels of monitoring and encouragement. Results from a one‐way ANOVA indicated that paternal caregivers with high (compared to moderate) levels of encouragement and monitoring were associated with youth who reported less depressive symptoms, higher levels of self‐efficacy, and less favorable attitudes toward deviance. Discriminant analysis results indicated that approximately half of the sample were correctly classified into two paternal caregiver classes. The findings provide evidence that some of these caregivers engage in parenting practices that support youths' psychological functioning. More research is needed to determine what accounts for the variability in levels of paternal encouragement and supervision, including environmental influences, particularly for paternal caregivers exhibiting moderate‐to‐low levels of paternal encouragement and monitoring.